The equation you use for the slope of this kind of problem is (y2-y1)/(x2-x1). x1 is the first X coordinate, x2 is the second, y1 is the first y coordinate, y2 is the second.
(5-3)/(2-2)
2/0
This equation has an UNDEFINED SLOPE, as it is just a vertical line.
Answer:
First model gets the equation: y = 2 . 2^z
Second model gets the equation: y = 4^z
Third model gets the equation: y: = 4 . 2^z
Answer:
D) y=-4x+2
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(-2-6)/(1-(-1))
m=-8/(1+1)
m=-8/2
m=-4
y-y1=m(x-x1)
y-6=-4(x-(-1))
y-6=-4(x+1)
y=-4x-4+6
y=-4x+2
Answer:
t5ju8i8
Step-by-step explanation:
Answer:6,2
Step-by-step explanation:you need to add each step and divide